A Pragmatic Study of the Impact of a Brief Mindfulness Intervention on Prisoners and Staff in a Category B Prison and Men Subject to Community-Based Probation Supervision. (January 2021) - Davies, Jason; Ugwudike, Pamela; Young, Hayley; Hurrell, Chloe; Raynor, Peter
Objectives: This article presents two studies assessing the impact of mindfulness in prison (prisoners and staff) and non-custodial settings. Method: Study 1—prisoners ( n  = 17) and staff ( n  = 15) in a UK prison completed a mindfulness program; 16 individuals acted as a single time point comparison. Data were collected using self-report, computer based and physiological measurement. Study 2—men under community probation supervision were allocated to mindfulness (completed, n  = 28) or TAU ( n  = 27). Data were collected using self-report mindfulness measures. Results: Study 1—statistically significant (increases in mindfulness skills (η 2 p  = .234 to η 2 p  = .388), cognitive control (η 2 p  = .28), and heart rate variability (SDNN; η 2 p  = .41) along with significant decreases in stress (η 2 p  = .398) were found. In study 2, the mindfulness group showed non-significant improvements in mindfulness skills. Conclusion: The findings suggest brief mindfulness interventions could make an important contribution to offender rehabilitation and custodial staff wellbeing.